Exposição de embriões e larvas de zebrafish a compostos bisfenólicos para elucidação de mecanismos neurotoxicológicos - Fonseca, Raphaela Soares (2018)
The increase of environmental pollutants sources directly affects the ecosystem and human health, mainly due to loss of soil and water quality. Among these toxic agents are included endocrine disruptors, which can cause changes in biochemical pathways and physiological changes in organisms. Studies with different forms of bisphenols, compounds present in many products of human consumption and the environment, had already demonstrated extremely adverse effects on behavior and gene expression of targets related to neural and endocrine systems during development. The zebrafish, Danio rerio, is an excellent model organism for studying neurotoxicity, due to its advantages with respect to specific aspects of their development and a low maintenance cost when compared to other vertebrate model organisms. This work proposes the investigation of the effects of bisphenol A (BPA), its chlorinated derivatives and its substitutes (BPS and BPF), toxicological and behavioral parameters combined with characterization of its potential underlying cellular and molecular mechanisms such as cell death and proteins and gene expression in the nervous and endocrine systems. After the embryo and larvae were exposed to different concentrations of BPA and its derivatives, morphological analyzes and embryo survival were carried out, as well as behavioral tests of locomotion and cognitive evaluation of the larvae. In the concentrantion curve of the different bisphenolic compounds, no significant difference was observed in the survival, teratogenesis and hatching of the animals, however, a significant increase was detected in the exploratory parameters of the BPA and BPF groups. When comparing the aversive behavior of the BPA with the DMSO, there was no statistical difference between the groups, whereas in the BPS an improvement in the escape response of the larvae occurred. Additionally, behavioral and locomotor activity analyzes will be performed in adult animals previously treated with the compounds studied during the initial development. In this way, it is expected to contribute to the current knowledge of neurotoxicity mechanisms related to endocrine disruption caused by contaminants of the bisphenol family.